Cradle-to-cradle recycling in terawatt photovoltaics: A vision of perpetual utility - Peters, Ian Marius; Hauch, Jens; Brabec, Christoph (Joule, 2024)
To achieve carbon neutrality, a significant increase in photovoltaic module production is needed, affecting material demand and recycling perspectives. Circular recycling is essential for managing the material flows of a multi-terawatt global photovoltaic fleet. Immediate action is required to prevent the accumulation of millions of tons of low-value waste. Circularity's importance is multi-faceted and varies across materials. Limited silver reserves and competition with other markets necessitate reducing or substituting silver. For polymers, constrained production capacities can also be mitigated through circular recycling. The photovoltaic industry's immense glass demand calls for circular recycling to avoid overwhelming alternative markets. Recycling silicon, aluminum, and copper is vital for the economic feasibility of recycling, especially if silver is replaced. Although prolonging module lifespan reduces yearly material needs and influx into the recycling stream, it might also postpone achieving carbon reduction goals.
CRIS-Team Scopus Importer:2024-04-26